Arousing Children's Motivation in Learning English during the Corona Virus Outbreak - Eleska Sukma Annisa (Institut Agama Islam Negeri Palopo, 2022)
Motivation is an important factor that determines a learner success in learning English. The purpose of this study is to find the teaching strategies to arouse young learner motivation in learning English during the corona virus outbreak in SDN 1 Singopuran. This is descriptive qualitative research in which the subject is an English teacher at SDN 1 Singopuran. The data were collected through observation, interview, and document analysis. They were then analyzed using descriptive interactive method. To maintain the data credibility, the research applied this theory to obtain data from various sources by different studies, having an interview with one of the English teacher and comparing the results of interviews with data obtained from observations. The results showed that the strategies to motivate young learners to learn English during the corona virus outbreak in SDN 1 Singopuran by using educational books, flashcards, songs, pictures, and giving rewards to increase their knowledge with quizzes related to materials and pictures.